Improving the Learning Achievement of Catholic Religious Education in Elementary School Students through the AMOS Method - Sihotang, Din Oloan; Waruwu, Ermina; Sitepu, Abdi Guna; Situngkir, Ramses Antonius (Department of Integrated Science, Faculty of Mathematics and Natural Sciences, Universitas Negeri Semarang in Collaboration with Perkumpulan Pendidikan IPA Indonesia, 2023)
The main issue in the process of Catholic Religious Education (PAK) learning at St. Antonius Bangun Mulia Catholic School in Medan is the suboptimal achievement of student learning outcomes. This is caused by the frequent use of lectures and assignments by PAK teachers. The dominance of such methods leads to boredom and disinterest among students in participating in the learning process. Another issue is the lack of creativity among PAK teachers in finding and implementing alternative teaching methods that can motivate students to engage in PAK learning. In response to these situations, the AMOS method can be used as an alternative method for PAK learning with the aim of improving student learning outcomes. The research subjects in this study were 22 fourth-grade students. The data for this research were obtained from observing the activities of the students and conducting final tests in each cycle. The research data were analyzed descriptively and qualitatively. The results of the study show that the application of the AMOS method can improve student learning outcomes. In the pre-cycle, the percentage of students who completed their learning was 18.18%, while those who did not complete it were 81.82%. In cycle 1, 94.46% of students completed their learning, while 5.54% did not. In cycle 2, 100% of students completed their learning. Based on these research findings, it can be concluded that the use of the AMOS method can improve the learning achievement of fourth-grade students at St. Antonius Bangun Mulia Catholic Elementary School in Medan.